Pengaruh Komitmen Organisasi Dan Iklim Organisasi Terhadap Kepuasan Kerja Pegawai Dinas Perhubungan - sri sri mulyani; Ariska Ariska (LPPM Universitas Dharma Andalas, 2022)
The results of this study partially indicate that organizational commitment has a significant effect on job satisfaction for Padang Pariaman Transportation Service employees with a t-count value of 9.355 which is greater than the t-table value of 2.051, while the significant value is 0.000, which is smaller than 0.05. Partially, organizational climate has a significant effect on job satisfaction for employees of the Padang Pariaman Transportation Service with a t-count value of 0.3207 which is smaller than the t-table value of 2.051, while a significant value of 0.003 is greater than 0.05. Organizational commitment and organizational climate simultaneously have a significant effect on job satisfaction for employees of the Padang Pariaman Transportation Service with a calculated f value of 360.353 greater than the f table value of 3.35, while a significant value of 0.000 is smaller than 0.05. Overall, the effect of organizational commitment and organizational climate on job satisfaction is 96.4%, while the remaining 3.6% is influenced by other factors not discussed in this study.